Prognostic value of the albumin-bilirubin score in patients with non-Hodgkin lymphoma-associated hemophagocytic lymphohistiocytosis - Cheng, Wanying; Duan, Limin; Xu, Ji; Shu, Yongqian; Qiu, Hongxia; Yin, Guangli (Frontiers in Immunology, 2023)
Secondary hemophagocytic lymphohistiocytosis (sHLH) is a rare life-threatening systemic disease. This study aimed to assess the prognostic value of pretreatment albumin-bilirubin (ALBI). We retrospectively analysed 168 non-Hodgkin lymphoma-associated secondary hemophagocytic lymphohistiocytosis (NHL-sHLH) patients with hepatic injuries. Multivariable logistic/Cox models and restricted cubic spline models were conducted to evaluate the relationships between the ALBI score and short- and long-term survival. Among 168 adult NHL-sHLH patients, 82 (48.8%) patients died within 30 days after admission, and 144 (85.7%) patients died during the follow-up period. Multivariable logistic/Cox regression model indicated that ALBI grade could be an independent risk factor for predicting the prognosis of patients with 30-day mortality and overall survival (odds ratios [OR]30 days 5.37, 95% confidence interval 2.41-12.64, P < 0.001; hazard ratios [HR]OS 1.52, 95% confidence interval 1.06-2.18, P = 0.023), respectively. The restricted cubic spline curve displayed a linear and positive relationship between the ALBI score and risk of mortality (P for nonlinearity =0.503). Furthermore, receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) for predicting mortality by integrative analysis of the ALBI score and ferritin was significantly improved compared to the ALBI score (AUC 30 days: 0.820 vs 0.693, P = 0.001; AUC1 year: 0.754 vs 0.681, P = 0.043) or ferritin (AUC30 days: 0.820 vs 0.724, P = 0.005; AUC1 year: 0.754 vs 0.658, P = 0.031) alone. The ALBI score could be a useful indicator of short and long-term survival for NHL-sHLH patients with hepatic injuries.